The history of Community Interpreting studies in Japan - Mizuno, Makiko (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The study of CI in Japan began in the late 1980s, and its first researchers were law professors and attorneys who advocated human rights. They discussed the plight of non-Japanese-speaking defendants in legal settings. Subsequently, interpreters and theorists of interpretation discussed ethics, cultural issues, training and so on. Recently, however , a new wave of studies has emerged, with a greaterfocus on linguistic approaches such as discourse analysis, corpus studies etc. This paper willfirst briefly review the earlier CI research in general and thenfocus on legal interpreting, which is the most advanced and noteworthy area of CIstudies in Japan.